JIHADIST GROUPS IN THE SAHEL. AN ETYMOLOGICAL ANALYSIS - Francesco Saverio Angió (Revista UNISCI, 2018)
The names of the insurgent groups include historical, cultural, ethnic, territorial and doctrinal references that appear too specific to be considered accidental and thus could be indicative of their strategy. The examples of terrorist attacks carried out by these groups support this argument, as they adopted or changed their name beforehand, shortly before a spinoff group, a new alliance or an offshoot emerged, or when an attack occurred in a non-traditional geographic area of action. Unfortunately, too often mass media and government officials utilise incorrect and/or superficial translations of these names, thus contributing to a lack of detailed information on the jihadists. The etymological analysis of the Arabic names of the Sahelian jihadist insurgents intends to and contributes to increase the knowledge on the nature and actions of these groups